The influence of N and S poles of static magnetic field (SMF) on Candida albicans hyphal formation and antifungal activity of amphotericin B - Sztafrowski, Dariusz (Folia Microbiol (Praha), 2019)
Due to the increasing number of Candida albicans’ infections and the resistance of this pathogenic fungus to drugs, new therapeutic strategies are sought. One of such strategies may be the use of static magnetic field (SMF). C. albicans cultures were subjected to static magnetic field of the induction 0.5 T in the presence of fluconazole and amphotericin B. We identified a reduction of C. albicans hyphal length. Also, a statistically significant additional effect on the viability of C. albicans was revealed when SMF was combined with the antimycotic drug amphotericin B. The synergistic effect of this antimycotic and SMF may be due to the fact that amphotericin B binds to ergosterol in plasma membrane and SMF similarly to MF could influence domain orientation in plasma membrane (PM).